2001
DOI: 10.1023/a:1012452705349
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The addition of sialic acid residues to glycoproteins can affect important protein properties including biological activity and in vivo circulatory half-life. For sialylation to occur, the donor sugar nucleotide cytidine monophospho-sialic acid (CMP-SA) must be generated and enzymatically transferred to an acceptor oligosaccharide. However, examination of insect cells grown in serum-free medium revealed negligible native levels of the most common sialic acid nucleotide, CMP-N-acetylneuraminic acid (CMP-Neu5Ac)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Localization of DmCSAS to the Secretory Compartment of the CellWhereas the mammalian sialic acid 9-phosphate synthase responsible for generating sialic acid is a soluble cytoplasmic enzyme (31), both human and murine CSAS, which activate the sialic acid with a nucleotide, have been reported to localize to the nucleus (22,23,33). As mentioned previously, murine CSAS possesses an N-terminal potential NLS, BC1, and an internal NLS, BC2 (22,29).…”
Section: Expression Of Dmcsas In Mammalian Cells Lacking Endogenousmentioning
confidence: 80%
See 1 more Smart Citation
“…Localization of DmCSAS to the Secretory Compartment of the CellWhereas the mammalian sialic acid 9-phosphate synthase responsible for generating sialic acid is a soluble cytoplasmic enzyme (31), both human and murine CSAS, which activate the sialic acid with a nucleotide, have been reported to localize to the nucleus (22,23,33). As mentioned previously, murine CSAS possesses an N-terminal potential NLS, BC1, and an internal NLS, BC2 (22,29).…”
Section: Expression Of Dmcsas In Mammalian Cells Lacking Endogenousmentioning
confidence: 80%
“…In Vitro CMP-sialic Acid Synthetase Assay-The in vitro CMP-sialic acid synthetase assay was performed as previously described (23). Briefly, 40 ml of cell lysate was added to the 100 l of substrate mixture (0.2 M Tris, 0.2 mM dithiothreitiol, 20 mM MgCl 2 , 5.5 mM CTP, and 2.8 mM Neu5Ac) and incubated for 40 min at 37°C.…”
Section: Forward Primersmentioning
confidence: 99%
“…The biosynthesis of N-acetylneuraminic acid (Neu5Ac) from ManNAc can be either achieved via phosphorylation by ManNAc 6-kinase and aldol addition of phosphoenolpyruvate (PEP) by sialic acid 9-P-synthase following an enzymatic dephosphorylation (Scheme 1, route A) [9,10], or the direct (reversible) aldol addition by sialic acid dephosphorylation (Scheme 1, route A) [9,10], or the direct (reversible) aldol addition by sialic acid aldolase (Scheme 1, route B) [11]. The resulting sialic acid is then converted into its activated precursor form CMP-N-acetylneuraminic acid and transported into the Golgi apparatus, where it is ultimately utilized by various sialyltransferases to decorate oligosaccharide chains [12]. As ManNAc is the sole carbohydrate precursor in the biosynthesis of N-acetylneuraminic acid, a better understanding of the ManNAc biosynthesis will therefore also lead to a more profound knowledge of the sialic acid metabolism in cells.…”
Section: Introductionmentioning
confidence: 99%
“…When insect cells are cultured in serum-free medium for the production of a recombinant glycoprotein, the inability to synthesize CMP-Neu5Ac becomes a key problem. In order to overcome this limitation, our group has cloned mammalian SAS (16) and CMP-SAS (17), and has introduced these into Sf9 cells. When cultured in serum-free medium supplemented with N-acetylmannosamine (ManNAc), a precursor of Neu5Ac, Sf9 cells expressing a human SAS produced a high level of Neu5Ac (16).…”
Section: E-4 Expression Of Sialylated N-glycansmentioning
confidence: 99%
“…When cultured in serum-free medium supplemented with N-acetylmannosamine (ManNAc), a precursor of Neu5Ac, Sf9 cells expressing a human SAS produced a high level of Neu5Ac (16). Furthermore, a high level of CMPNeu5Ac production can be achieved by co-infecting two diŠerent baculoviruses, each encoding SAS or CMP-SAS, in Sf9 cells with ManNAc supplement in the culture medium (17). In a more recent study, our group has shown that ManNAc supplementation could be superseded by expressing UDP-GlcNAc 2-epimerase/ManNAc kinase in combination with SAS and CMP-SAS, with or without supplementation of less expensive GlcNAc (77).…”
Section: E-4 Expression Of Sialylated N-glycansmentioning
confidence: 99%